Adaptation level as the basic health status characteristics: possibilitics of its assessment and forecasting of desadaptation violations - Vysochyna I.L. (Medičnì Perspektivi)
On the basis of comprehensive survey with integrative assessment of health state (medical history data, physical examination, anthropometry, battery of psychological tests (Eysenck, Shmishek’s Personality Inventory (teen version), tapping - test by E.P. Ilyin, children's questionnaire of neuroses; test for rapid assessment of health, activity and mood, anxiety diagnosis by Spielberg - Khanin; Luscher test, color relations test) level of adaptation was defined in 236 children from orphanages aged from 4 to 18 years. The manifestations of maladjustment were registered both on psychological level (neuroticism, high anxiety, decreased performance, activity and psychological endurance, sleep disturbance, presence of accentuation and neurotic disorders) and somatic level (recurrent acute respiratory infections, poor physical development, exacerbation of chronic foci of infection and burdened biological history); this summarizes conclusions on a low level of health status of children in orphanages. The author has developed mathematical models of adaptation assessment and prediction of desadaptation, which allowed to identify children at risk for the development of adaptation disorders and children with maladjustment; according to the level and severity of maladaptive disorders correction programs are designed.